2020
DOI: 10.34293/education.v8i4.3294
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Peer Instruction Method in Programming Education to Student’s Attitudes towards Course and Programming Self-Efficacy

Abstract: In this research, the effect of using the peer instruction method in programming teaching on the secondary school student’s attitudes towards information technologies and software course and their perception of programming self-efficacy comparing to traditional teaching methods are examined. In the study, the “mixed method,” in which qualitative and quantitative research approaches were utilized together, was used. In the quantitative part of the research, the pretest-posttest control group and semi-experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Three out of the four showed statistical significance in the effect or correlation between peer tutoring and academic performance [25,26,28]. The perception of the positive effect of peer tutoring on students' attitude and confidence is further confirmed by other studies using mixed methods [29,30], convenience sampling [31], and experience reports [32,33].…”
Section: Figure 2 Subjects Taught In Peer Tutoring Articlessupporting
confidence: 60%
See 1 more Smart Citation
“…Three out of the four showed statistical significance in the effect or correlation between peer tutoring and academic performance [25,26,28]. The perception of the positive effect of peer tutoring on students' attitude and confidence is further confirmed by other studies using mixed methods [29,30], convenience sampling [31], and experience reports [32,33].…”
Section: Figure 2 Subjects Taught In Peer Tutoring Articlessupporting
confidence: 60%
“…[26] Journal Discrete Structures Quasi-Experimental n=60 Students exposed to peer tutoring had significantly higher achievements than those in conventional teaching. [30] Journal Programming Mixed method n=72…”
Section: Discussionmentioning
confidence: 99%
“…This fostered teamwork, communication, and critical thinking skills through group discussions and projects. Strong support for Step 8 is found in the literature, with Yildiz and Gündüz (2020) determining that peer instruction has a positive and significant effect on secondary school computer programming teaching and student programming self-efficacy (PSE). The authors also indicated that peer instruction positively affected student PSE perceptions, which was greater than traditional teaching methods.…”
Section: Collaborative Learning Opportunitiesmentioning
confidence: 99%
“…Finally, Yildiz and Gündüz (2020) examined how peer instruction affected secondary school computer programming teaching and student PSE. Results showed that peer instruction increases students' PSE perceptions greater than traditional teaching methods.…”
Section: Pse's Global Importancementioning
confidence: 99%